2018
DOI: 10.1093/eurpub/cky165
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequality in non-communicable diseases in Europe between 2004 and 2015: evidence from the SHARE survey

Abstract: To prevent chronic diseases, health policy should aim not only to improve individual health behaviours in the population, but also to reduce socioeconomic inequality. Our study suggests promoting a healthy lifestyle in the most disadvantaged socioeconomic classes as a strategy to improve the health conditions of the whole population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…For both SPH and NCDs, income did not play any role. This result is in line with other literature using the SHARE dataset, as it was found that both the number of NCDs and socioeconomic inequality in NCDs were more likely to be related to differences in education than income [50].…”
Section: Discussionsupporting
confidence: 93%
“…For both SPH and NCDs, income did not play any role. This result is in line with other literature using the SHARE dataset, as it was found that both the number of NCDs and socioeconomic inequality in NCDs were more likely to be related to differences in education than income [50].…”
Section: Discussionsupporting
confidence: 93%
“…Obesity is significantly associated with all-cause mortality [ 9 ] for example by increased rates of diabetes, cardiovascular disease and cancer. Where there is strong social patterning of obesity it is likely to make an increasing contribution to health inequalities [ 10 ]. A European study used population attributable fractions and rate ratios from the literature to estimate how a scenario elimination of differences in obesity by education would decrease relative inequality in all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In Hong Kong, the association between ST and the weight outcomes was stronger in lower-educated than in higher-educated participants, while no moderating effect of educational level was found in Ghent. In general, lower-educated individuals often have a less healthy lifestyle than their higher-educated counterparts [52,53]. Thus, it is possible that higher-educated Hong Kong older adults might have compensated for the negative effects of ST by following a healthier diet.…”
Section: Discussionmentioning
confidence: 99%